Biogenic fabrication of S-scheme NiO–FeWO4 heterojunction nanocomposite using Cassava (Manihot esculenta Crantz) leaf extract for visible-light-driven dye degradation: synthesis, characterisation and photocatalytic evaluation - Lee, Fatimah; Abdullah, Luqman Chuah; Ramli, Irmawati; Shamsuri, Ahmad Adlie; Daik, Rusli; Mohd Noor, Ikhwan Syafiq; Md Jamil, Siti Nurul Ain (Elsevier, 2025)
Industrial dye effluents such as methylene blue (MB) resist biodegradation, generate carcinogenic intermediates and bioaccumulate in ecosystems, demanding advanced remediation strategies. Photocatalysis utilizing semiconductor-based materials as photocatalysts offers a sustainable route. Nickel oxide (NiO), a p-type semiconductor, exhibits excellent hole mobility, however suffers from wide bandgap, limited to UV-light activity and rapid charge recombination. In this study, coupling NiO with a narrow bandgap n-type semiconductor, iron (II) tungstate (FeWO4) has successfully extended its light absorption and enhances charge separation, improving the photocatalytic activity of NiOnps. An S-scheme NiO-FeWO4 heterojunction nanocomposite was fabricated via PEG-200 binder-assisted physical coupling technique, using Cassava leaves extract (CMLE) as a natural reducing and stabilising agent. FTIR analysis confirms the coupling of NiOnps and FeWO4nps through vibrational modes of Ni-O, Fe-O, W-O and O-WO bonds. XRD analysis shows an enhanced crystallinity of NiO-FeWO4 heterojunction nanocomposite (88.73 %) compared to pristine NiOnps (75.14 %) and FeWO4nps (66.54 %). FESEM and HRTEM images of NiO-FeWO4 depict a clear interfacial contact of granular FeWO4nps onto rod-like NiOnps, with narrow PDI values indicating the feasibility of CMLE to maintain size uniformity. The p-n heterojunction formation significantly reduced the bandgap energy from 2.82 eV to 2.10 eV, suppressed PL intensity, depleted charge transfer resistance and enhanced photocurrent response. Hence, NiO-40FeWO4 nanocomposite demonstrates outstanding photocatalytic performance under visible light irradiation towards MB (10 ppm) degradation (96.72 %) with a rate constant of 0.04996 min−1, far surpassing pristine NiOnps (21.90 %, 0.0035 min−1) and FeWO4nps (60.45 %, 0.0023 min−1). This work presents a synergistic strategy that integrates biogenic synthesis and capability of binder-assisted coupling technique to design heterojunction formation, yielding a robust photocatalyst with enhanced structural, electronic and optical properties for sustainable wastewater remediation.